Ziegler-Natta catalyst for ethylene polymerization and in-situ grafting as well as preparation method and application of Ziegler-Natta catalyst

By introducing free radical initiator into Ziegler-Natta catalyst and preparing the catalyst by spray drying, the problems of uneven grafting and low grafting rate in the existing polyethylene grafting methods are solved, and a more efficient and uniform grafting reaction and a simplified preparation process are achieved.

CN119775496AActive Publication Date: 2025-04-08CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311291903.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-08
Publication Date
2025-04-08
Estimated Expiration
2043-10-08

AI Technical Summary

Technical Problem

The existing polyethylene grafting methods have problems such as uneven grafting, low grafting rate, large equipment investment, numerous operations and unfriendly environment.

Method used

A Ziegler-Natta catalyst for ethylene polymerization and in-situ grafting is used. The catalyst introduces a radical initiator during the preparation process and is prepared by spray drying. The catalyst has good particle shape and narrow particle size distribution. The particle size can be adjusted according to needs and the grafting rate can be improved.

Benefits of technology

The grafting reaction is achieved more uniform, the grafting rate is higher, and the gel content is lower. The preparation process of grafted polyethylene is simplified, and the product flowability is not required.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004483273990000131
    Figure BDA0004483273990000131
  • Figure BDA0004483273990000141
    Figure BDA0004483273990000141
  • Figure BDA0004483273990000142
    Figure BDA0004483273990000142
Patent Text Reader

Abstract

The invention relates to the field of polyolefin catalysts, in particular to a Ziegler-Natta catalyst for olefin polymerization and in-situ grafting as well as a preparation method and application of the Ziegler-Natta catalyst. The Ziegler-Natta catalyst comprises blending components and / or reaction products including the following raw materials: a carrier, a titanium element source, a magnesium element source, an electron donor and a free radical initiator. The free radical initiator is introduced in the preparation process of the catalyst, the preparation process is relatively simple, the polar monomer is initiated to be grafted on the polyethylene, the grafting reaction is more uniform, the dosage of the free radical initiator is small, the grafting efficiency is higher, and the gel content is lower; the particle size of the catalyst can be adjusted according to use requirements, so that the particle size of a polymer is regulated and controlled, and the grafting efficiency is improved; by using the catalyst, grafted polyethylene can be directly obtained through a one-step method, a grafted product does not need to be dried and separated, and the preparation process of the grafted polyethylene is simplified.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polyolefin catalysts, and in particular to a Ziegler-Natta catalyst for olefin polymerization and in-situ grafting, and a preparation method and application thereof. Background Art

[0002] Polyethylene is one of the most produced plastic products in the world, so it is widely used in various fields. However, its complete lack of polarity and low surface energy limit its wider application. In order to solve this problem, polyethylene is grafted and modified to introduce polar groups on the molecular chain. The polarity and functionality of the polar groups can improve its performance deficiencies.

[0003] Catalysts are the key technology in the polyolefin industry, among which Ziegler-Natta catalyst is the most mature system. Its high activity, high hydrogen sensitivity and controllable molecular weight distribution make it dominant in the polyethylene industry (Polymer Bulletin 2021, (6): 15-24).

[0004] The commonly used polyethylene grafting methods are: 1. Melt grafting. This is the most commonly used and most researched chemical grafting method. The polyethylene in a molten state is grafted with the grafting monomer in an extruder under the action of an initiator; 2. Solution grafting. This refers to dissolving polyethylene, polar monomers and initiators in a reaction medium for grafting reaction; 3. Solid phase grafting. This is to place polyethylene powder directly with initiators, grafting monomers, surfactants, etc. for contact reaction; 4. Radiation grafting. This method uses high-energy gamma rays or ultraviolet rays as radiation energy. The irradiated polyethylene produces free radicals, which are then polymerized with the grafting monomer to obtain a grafted free radical initiator. The above methods all involve secondary reactions of the finished polyethylene to obtain grafted polyethylene (Plastics Science and Technology, 2005 (2): 42-46).

[0005] Among them, the melting method requires large equipment investment, and the gel content is high due to the high preparation temperature; the solid phase grafting method has many advantages such as simple operation, short reaction time, no need for large equipment and therefore low investment, no need for reaction medium and therefore no need for solvent recovery and other operation steps, and has high practical value. However, this method also has disadvantages: the reaction is a heterogeneous system and a local modification method, so it is prone to problems such as uneven grafting and low grafting rate. The radiation method also has such problems; and although the solution method is a homogeneous system and can obtain uniform grafted products, the products need to be dried and separated, which requires many operations and is not environmentally friendly. Summary of the invention

[0006] Based on this, the present invention provides a Ziegler-Natta catalyst for ethylene polymerization and in-situ grafting and a preparation method thereof. The catalyst introduces a free radical initiator during the preparation process, and the preparation process is relatively simple. First, the Ziegler-Natta catalyst is responsible for catalyzing ethylene polymerization, and the free radical initiator is evenly dispersed in the polyethylene powder at this time, and then the free radical initiator initiates the polar monomer to be grafted on the polyethylene, and the grafting reaction is more uniform, the amount of free radical initiator is small, the grafting rate efficiency is higher, and the gel content is lower; on the other hand, the catalyst is prepared by a spray drying method, and the catalyst not only has a good particle shape, but also can adjust the catalyst particle size according to the use requirements, thereby regulating the polymer particle size and improving the grafting efficiency; the catalyst can be used to directly obtain grafted polyethylene by a one-step method, and the grafted product does not need to be dried and separated, simplifying the preparation process of grafted polyethylene.

[0007] The first aspect of the present invention is to provide a Ziegler-Natta catalyst, comprising a blended component and / or a reaction product including the following raw materials:

[0008] A carrier, a titanium source, a magnesium source, an electron donor and a free radical initiator.

[0009] According to a preferred embodiment of the present invention, the carrier is selected from inorganic oxide carriers, preferably silicon oxide and / or aluminum oxide, more preferably silicon dioxide.

[0010] According to a preferred embodiment of the present invention, the particle size of the inorganic oxide carrier is 0.01 to 5 μm, preferably 0.01 to 2 μm.

[0011] According to an embodiment of the present invention, the free radical initiator is selected from at least one of azo and peroxide initiators. According to a preferred embodiment of the present invention, the free radical initiator is preferably selected from at least one of benzoyl peroxide, diisopropylbenzene peroxide, di-tert-butyl peroxide, tert-butyl hydroperoxide, tert-butyl perbenzoate, diisobutyl peroxydicarbonate, azobisisobutyronitrile and azobisisoheptylonitrile.

[0012] According to an embodiment of the present invention, the titanium source is a titanium-containing compound; preferably, the titanium-containing compound is at least one selected from titanium halides, products of titanium halides reduced by aluminum, and products of titanium halides reduced by magnesium.

[0013] The general formula of the titanium-containing compound is Ti(OR 4 ) a X b , Ti(OR 4 ) a X b Medium R 4 C1-C 10aliphatic or aromatic hydrocarbon group, X is halogen, preferably fluorine, chlorine or bromine, a is 0, 1 or 2, b is an integer from 1 to 4, and a+b=3 or 4; preferably, R 4 Selected from C1-C6 alkyl, C2-C6 alkenyl, C3-C 10 Cycloalkyl or C6-C 10 An aromatic hydrocarbon group; preferably, R 4 is selected from methyl, ethyl, n-propyl, n-butyl, n-pentyl, n-hexyl, cyclopropyl, methylcyclopropyl, n-pentyl, methylcyclopentyl, cyclohexyl, phenyl, benzyl or xylyl.

[0014] According to an embodiment of the present invention, the magnesium source is a magnesium halide; preferably, the magnesium halide is selected from at least one of magnesium fluoride, magnesium chloride, magnesium bromide and magnesium iodide.

[0015] According to an embodiment of the present invention, the electron donor is selected from at least one of C1-C4 saturated fatty carboxylic acid alkyl esters, C7-C8 aromatic carboxylic acid alkyl esters, C2-C6 fatty ethers, C3-C4 cyclic ethers and C3-C6 saturated fatty ketones. Preferably, it is at least one of methyl formate, ethyl acetate, butyl acetate, ethyl ether, hexyl ether, tetrahydrofuran, acetone and methyl isobutyl ketone, etc. These electron donor compounds can be used alone or in combination.

[0016] According to a preferred embodiment of the present invention, based on the total weight of the Ziegler-Natta catalyst as 100wt%, the Ziegler-Natta catalyst comprises: titanium element: 0.5-4wt%; magnesium element: 2-8wt%; electron donor: 10-35wt%; free radical initiator: 10-60wt%; carrier: 10-60wt%.

[0017] According to a preferred embodiment of the present invention, the average particle size of the Ziegler-Natta catalyst is 7 to 100 μm, preferably 8 to 50 μm.

[0018] In a preferred embodiment of the present invention, the average particle size of the supported post-transition metal catalyst is 7 to 100 μm. The inventors of the present invention have found through research that, based on the catalyst formulation of the present invention, by further adjusting the average particle size of the catalyst, the grafting rate of the grafted polyethylene can be adjusted. Within the preferred average particle size range of the present invention, a grafted polyethylene with a high grafting rate can be obtained while maintaining a certain polymerization activity. More preferably, the average particle size of the catalyst is 8 to 50 μm, which can further improve the grafting rate. Further more preferably, the average particle size of the catalyst is 8 to 30 μm; more preferably, the average particle size of the supported post-transition metal catalyst is 8-20 μm. Under the condition of a further lower average particle size, the grafted polyethylene has a further higher grafting rate; preferably 8-15 μm.

[0019] According to the present invention, in order to further improve the uniformity of the particle size of the obtained grafted polyethylene and make the particle size distribution narrower, in a preferred embodiment of the present invention, the particle size distribution of the Ziegler-Natta catalyst is less than 2, preferably less than 1.5.

[0020] The particle size refers to the average particle size, that is, the equivalent diameter of the largest particle when the cumulative distribution is 50% in the particle size distribution curve (d 50 ). Particle size distribution refers to the diameter distance, that is, (d 90 -d 10 ) / d 50 ), which describes how broad the particle distribution is.

[0021] The second aspect of the present invention is to provide a method for preparing the Ziegler-Natta catalyst according to the first aspect, comprising the following steps:

[0022] (1) mixing raw materials including a titanium source, a magnesium source, an electron donor, a free radical initiator, a carrier and an optional organic solvent to obtain a slurry suspension;

[0023] (2) spray drying the slurry suspension obtained in step (1) to obtain the Ziegler-Natta catalyst.

[0024] According to a preferred embodiment of the present invention, the preparation of the slurry suspension in step (1) includes: first mixing a titanium source, a magnesium source and an electron donor, treating at 20-85°C for 0.5-3h to obtain a mother liquor; adding a carrier and a free radical initiator during or after the preparation of the mother liquor, and mixing for 2-12h.

[0025] According to a preferred embodiment of the present invention, the spray drying conditions in step (2) are: inlet temperature 50-200°C, outlet temperature 30-150°C.

[0026] According to the present invention, the particle size of the catalyst obtained can be adjusted by the air flow rate of the spray drying nozzle. According to a preferred embodiment of the present invention, the air flow rate of the spray drying nozzle in step (2) is 10-50m 3 / h, more preferably 21-50m 3 / h, and more preferably 26-50m 3 / h.

[0027] According to a preferred embodiment of the present invention, in step (1), relative to 1g of the carrier, the amount of the electron donor is 5 to 100mL, preferably 10 to 50mL, for example, 10mL, 20mL, 30mL, 40mL, mL, 50mL, and any two values ​​or any interval between any two values; and / or, the mass ratio of the carrier to the free radical initiator is (0.1 to 50):1, preferably (0.3 to 10):1, for example, 0.3:1, 0.5:1, 1:1, 1.5:1, 2:1, 4:1, 6:1, 8:1, etc. :1, 10:1; and any two values ​​or any interval between any two values; and / or, the molar ratio of the titanium element in the titanium source to the magnesium element in the magnesium source is (0.1-0.5):1, for example, 0.1, 0.2, 0.3, 0.4, 0.5, and the ratio of any two values ​​or any interval between any two values ​​to 1; and / or, the mass ratio of the carrier to the magnesium source is (0.5-6):1, for example, 0.5, 1, 2, 3, 4, 5, 6 and the ratio of any two values ​​or any interval between any two values ​​to 1.

[0028] According to a more preferred embodiment of the present invention, in step (1), the amount of the electron donor is 5 to 100 mL, preferably 10 to 50 mL, relative to 1 g of the carrier; the mass ratio of the carrier to the free radical initiator is (0.1 to 50):1, preferably (0.3 to 10):1; the molar ratio of the titanium element in the titanium source to the magnesium element in the magnesium source is (0.1 to 0.5):1; the mass ratio of the carrier to the magnesium source is (0.5 to 6):1.

[0029] According to a preferred embodiment of the present invention, the molar ratio of the electron donor to the magnesium element in the magnesium source is (10-45):1, for example, 10, 20, 30, 40, 45, and the ratio of any two values ​​or any interval between any two values ​​to 1.

[0030] In step (1), an organic solvent is optionally added to form a uniform slurry. The organic solvent used can be an organic solvent commonly used in the art, preferably selected from at least one of alkanes, halogenated alkanes, aromatic hydrocarbons, heterocyclic compounds, ethers, ketones, and esters, and more preferably at least one of pentane, hexane, heptane, dichloromethane, chloroform, benzene, toluene, chlorobenzene, chlorotoluene, tetrahydrofuran, acetone, ether, and ethyl acetate; based on 1g of the carrier, the amount of the organic solvent is 5 to 100mL, preferably 10 to 50mL. The organic solvent and the electron donor can be added at the same time. When the electron donor can also serve as an organic solvent to dissolve raw materials such as a magnesium source, only the electron donor can be added. For example, in an embodiment of the present invention, tetrahydrofuran is both an electron donor and an organic solvent, and no additional organic solvent needs to be added.

[0031] The third aspect of the present invention is to provide a catalyst for olefin polymerization, comprising:

[0032] (A) the Ziegler-Natta catalyst described in the first aspect or the Ziegler-Natta catalyst obtained by the preparation method described in the second aspect;

[0033] (B) The general formula is A1R b X' 3b An organoaluminum compound, wherein R is hydrogen or a hydrocarbon group having 120 carbon atoms; X' is a halogen; and 0<b≤3.

[0034] According to a preferred embodiment of the present invention, the organic aluminum compound is at least one selected from triethylaluminum, triisobutylaluminum, tri-n-hexylaluminum, tri-n-octylaluminum and diethylaluminum monochloride.

[0035] According to a preferred embodiment of the present invention, the molar ratio of the organic aluminum compound to the titanium element in the Ziegler-Natta catalyst is (5-1000):1.

[0036] The fourth aspect of the present invention is to provide a use of the Ziegler-Natta catalyst described in the first aspect, or the Ziegler-Natta catalyst prepared by the preparation method described in the second aspect, or the catalyst described in the third aspect in olefin polymerization.

[0037] According to a preferred embodiment of the present invention, the application of the Zigler-Natta catalyst in olefin polymerization comprises:

[0038] 1) Ethylene is reacted with a Ziegler-Natta catalyst and a general formula of A1R b X' 3bcontacting the organic aluminum compound, and / or contacting ethylene with the catalyst described in the third aspect to carry out ethylene polymerization to obtain polyethylene powder containing a free radical initiator;

[0039] 2) contacting the polar monomer with the polyethylene powder containing the free radical initiator obtained in 1) so that the free radical initiator initiates in-situ grafting of the polar monomer on the polyethylene; preferably,

[0040] The polar monomer is a compound containing a double bond and a polar group, preferably at least one of acrylic acid and its derivatives or esters, maleic anhydride or esters, maleate, alkenyl bisphenol A ether, acrylonitrile, styrene and its homologues, and glycidyl methacrylate.

[0041] The methods of ethylene polymerization and in-situ grafting in the present invention include but are not limited to ethylene slurry polymerization and grafting reaction.

[0042] For example, in ethylene slurry polymerization and grafting reaction, the conditions for ethylene polymerization reaction include:

[0043] The temperature is 40-100°C, the reaction time is 0.5-3h, the pressure is 0.5-3MPa, and the amount of Zigler-Natta catalyst used is 20-500mg. It is preferably carried out in the presence of alkyl aluminum.

[0044] The alkylaluminum can be selected from at least one of sesquiethylaluminum chloride, triethylaluminum, triisobutylaluminum, tri-n-hexylaluminum, etc., and / or, relative to 1 mol of titanium content in the catalyst, the amount of the alkylaluminum is 10-1000 mol.

[0045] The conditions of the ethylene polymerization reaction are such that the content of the free radical initiator in the obtained polyethylene powder containing the free radical initiator is 0.1-10 wt %.

[0046] The functions of alkyl aluminum or methyl chloroform are (1) to act as a scavenger to remove water and oxygen in the reaction process to avoid interference with the polymerization reaction; and (2) to stimulate the catalyst to carry out the polymerization reaction.

[0047] As an example, during the ethylene slurry polymerization and grafting reaction, the conditions for the in-situ grafting reaction include:

[0048] The temperature is 80-150℃, the reaction time is 2-8h, and the pressure is 1-5MPa.

[0049] The mass ratio of the polyethylene powder containing the free radical initiator to the polar monomer is 500-50:1.

[0050] The present invention provides a Ziegler-Natta catalyst for ethylene polymerization and in-situ grafting and a preparation method thereof. A free radical initiator is introduced into the catalyst during the preparation process. First, the Ziegler-Natta catalyst catalyzes ethylene polymerization. After the reaction, the free radical initiator is evenly dispersed in polyethylene powder. Then, the free radical initiator triggers the in-situ grafting of polar monomers on polyethylene, which makes the grafting reaction more uniform, the grafting rate is higher, and the gel content is lower. On the other hand, the catalyst is prepared by a spray drying method. The catalyst not only has a good particle shape and a narrow particle size distribution, but also can adjust the catalyst particle size according to the use requirements, so that the polyethylene powder particle size is reduced, thereby improving the grafting rate. The catalyst can be used to directly obtain grafted polyethylene through a one-step method to obtain a polymer powder with good fluidity, without the need for drying and separation, thereby simplifying the preparation process of grafted polyethylene.

[0051] Compared with the prior art, the present invention has the following advantages:

[0052] (1) The Ziegler-Natta catalyst for ethylene polymerization and in-situ grafting provided by the present invention is added with a free radical initiator during the loading process, and after initiating ethylene polymerization, the free radicals can be evenly dispersed inside the polyethylene, thereby initiating in-situ polar monomer grafting, and polar grafted polyethylene can be directly obtained in one step;

[0053] (2) The Ziegler-Natta catalyst for ethylene polymerization and in-situ grafting provided by the present invention uses less initiator in the preparation process of grafted polyethylene, the grafting reaction is more uniform, the grafting rate is higher, and the gel content is lower;

[0054] (3) The Ziegler-Natta catalyst provided by the present invention is used for olefin polymerization to obtain a resin powder having good particle morphology and high bulk density. The product does not need to be dried and separated and can be used in a slurry polymerization process.

[0055] (4) The preparation method of the Ziegler-Natta catalyst for ethylene polymerization and in-situ grafting provided by the present invention is simple, the catalyst particles have good morphology, the particle size can be adjusted within a large range, the particle size distribution is narrow, and the catalyst particle size can be adjusted according to the use requirements, so that the particle size of the polyethylene powder is reduced, thereby improving the grafting rate. DETAILED DESCRIPTION

[0056] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0057] The test instruments and test conditions used in the examples are as follows:

[0058] Determination of grafting rate (DG): Take 0.5g grafted sample, heat to reflux, dissolve in 70mL xylene, add 15mL KOH-methanol standard solution while hot, continue to reflux for 2h, add 2 drops of phenolphthalein reagent, titrate with standard HCl-isopropanol solution, and titrate the blank sample at the same time to calculate the grafting rate. It is calculated as the mass of maleic anhydride per 100g sample.

[0059] Determination of gel content (DC): A small amount of grafted sample is placed in a filter cloth bag, placed in a Soxhlet extractor, and refluxed with xylene for more than 12 hours. Then the filter cloth bag is taken out and dried in an oven at 80°C until the mass is constant. DC is calculated as the mass (g) of gel in 100g of sample, see formula (1).

[0060] DC=(m3-m2) / (m1-m2) (1)

[0061] In the formula: m1 is the mass of the filter cloth bag after loading the sample, g; m2 is the mass of the filter cloth bag, g; m3 is the total mass after extraction and drying, g.

[0062] Particle size and particle size distribution: The particle size and particle size distribution of the catalyst were tested using a Malvern MS3000 laser particle size distribution analyzer;

[0063] Metal content in the catalyst: The metal content in the catalyst was tested using an inductively coupled plasma mass spectrometer ICP-MS (Agilent 7500CX).

[0064] Determination of initiator content in the catalyst: Liquid nuclear magnetic resonance (Bruker AVANCE 300) was used for determination with hydroquinone as the internal standard.

[0065] Example 1

[0066] 1. Preparation of catalyst: In a 250mL four-necked flask equipped with a temperature controller, a stirrer, a reflux condenser, and nitrogen-purged and protected, 120mL of tetrahydrofuran (THF), 4.2g of magnesium chloride and 1.0mL of TiCl4 were added successively under stirring, and the temperature was raised to 65°C under stirring, and the reaction was refluxed at a constant temperature for 4 hours to obtain a mother liquor; then 5.5g of silica gel and 5.0g of benzoyl peroxide were added, and the constant temperature reflux stirring was continued at 65°C for 2 hours to completely disperse the silica gel in the mother liquor to obtain a slurry suspension; in a closed-loop circulating airflow spray dryer, nitrogen with an inlet temperature of 140°C was introduced into the spray dryer, and the obtained slurry suspension was added to the circulating dryer, the outlet temperature was 95°C, and the inlet nitrogen flow rate was controlled to be 31.0m 3 / h to obtain a solid catalyst component, some of its physical property parameters are shown in Table 1.

[0067] 2. Ethylene slurry polymerization and grafting reaction: 1L hexane was added to a 2L polymerization kettle that was first purged with nitrogen and then with hydrogen, and 1mL triethylaluminum (1M) and 100mg dry powder catalyst (i.e., solid catalyst component) were added at the same time. Hydrogen was added to 0.28MPa. After hydrogenation, ethylene was added to 1.03MPa, and the temperature was raised to 50°C. After reacting at 50°C at a constant temperature and pressure for 0.5h, the ethylene in the kettle was replaced with nitrogen and the pressure was raised to 2MPa. Then 6.0g methyl methacrylate was added, the temperature was raised to 125°C, and the reaction was continued for 5h before cooling and discharging. The assessment results are shown in Table 2.

[0068] Example 2

[0069] 1. Preparation of catalyst: In a 250mL four-necked flask equipped with a temperature controller, a stirrer, a reflux condenser, and nitrogen-purged and protected, 120mL of tetrahydrofuran (THF), 4.2g of magnesium chloride and 1.0mL of TiCl4 were added successively under stirring, and the temperature was raised to 65°C under stirring, and the reaction was carried out under constant temperature reflux for 4 hours to obtain a mother liquor; then 5.5g of silica gel and 7.0g of benzoyl peroxide were added, and constant temperature reflux stirring was continued at 65°C for 2 hours to completely disperse the silica gel in the mother liquor to obtain a slurry suspension; in a closed-loop circulating airflow spray dryer, nitrogen with an inlet temperature of 140°C was introduced into the spray dryer, and the obtained slurry suspension was added to the circulating dryer, the outlet temperature was 95°C, and the inlet nitrogen flow rate was controlled to 31.0m 3 / h to obtain a solid catalyst component, some of its physical property parameters are shown in Table 1.

[0070] 2. Ethylene slurry polymerization and grafting reaction: 1L hexane was added to a 2L polymerization kettle that was first purged with nitrogen and then with hydrogen, and 1mL triethylaluminum (1M) and 100mg dry powder catalyst were added at the same time. Hydrogen was added to 0.28MPa. After the hydrogenation was completed, ethylene was added to 1.03MPa, and the temperature was raised to 50°C. After the reaction was carried out at a constant temperature and pressure of 50°C for 0.5h, the ethylene in the kettle was replaced with nitrogen and the pressure was raised to 2MPa. Then 8.0g methacrylic acid was added, the temperature was raised to 125°C, and the reaction was carried out for 5h before the temperature was lowered and the material was discharged. The assessment results are shown in Table 2.

[0071] Example 3

[0072] 1. Preparation of catalyst: In a 250mL four-necked flask equipped with a temperature controller, a stirrer, a reflux condenser, and nitrogen purged and protected, 120mL tetrahydrofuran (THF), 4.2g magnesium chloride and 1.0mL TiCl4 were added successively under stirring, and the temperature was raised to 65°C under stirring, and the reaction was refluxed at a constant temperature for 4 hours to obtain a mother liquor; then 3.0g silica gel and 6.0g azobisisobutyronitrile were added, and the constant temperature reflux stirring was continued at 65°C for 2 hours to completely disperse the silica gel in the mother liquor to obtain a slurry suspension; on a closed-loop circulating airflow spray dryer, nitrogen with an inlet temperature of 140°C was introduced into the spray dryer, and the obtained slurry suspension was added to the circulating dryer, the outlet temperature was 95°C, and the inlet nitrogen flow rate was controlled to 25.4m 3 / h to obtain a solid catalyst component, some of its physical property parameters are shown in Table 1.

[0073] 2. Ethylene slurry polymerization and grafting reaction: 1L hexane was added to a 2L polymerization kettle that was purged with nitrogen first and then hydrogen, and 1mL triethylaluminum (1M) and 100mg dry powder catalyst were added at the same time. Hydrogen was added to 0.28MPa. After hydrogenation, ethylene was added to 1.03MPa, and the temperature was raised to 50°C. After reacting at 50°C at a constant temperature and pressure for 0.5h, the ethylene in the kettle was replaced with nitrogen and the pressure was raised to 2MPa. Then 10g diethyl maleic anhydride was added, the temperature was raised to 125°C, and the reaction was continued for 5h before cooling and discharging. The assessment results are shown in Table 2.

[0074] Example 4

[0075] 1. Preparation of catalyst: In a 250mL four-necked flask equipped with a temperature controller, a stirrer, a reflux condenser, and nitrogen-purged and protected, 120mL of tetrahydrofuran (THF), 4.2g of magnesium chloride and 1.0mL of TiCl4 were added successively under stirring, and the temperature was raised to 65°C under stirring, and the reaction was carried out under constant temperature reflux for 4 hours to obtain a mother liquor; then 3.0g of silica gel and 8.0g of azobisisobutyronitrile were added, and constant temperature reflux stirring was continued at 65°C for 2 hours to completely disperse the silica gel in the mother liquor to obtain a slurry suspension; in a closed-loop circulating airflow spray dryer, nitrogen with an inlet temperature of 140°C was introduced into the spray dryer, and the obtained slurry suspension was added to the circulating dryer, the outlet temperature was 95°C, and the inlet nitrogen flow rate was controlled to 25.4m 3 / h to obtain a solid catalyst component, some of its physical property parameters are shown in Table 1.

[0076] 2. Ethylene slurry polymerization and grafting reaction: 1L hexane was added to a 2L polymerization kettle that was purged with nitrogen first and then hydrogen, and 1mL triethylaluminum (1M) and 100mg dry powder catalyst were added at the same time. Hydrogen was added to 0.28MPa. After hydrogenation, ethylene was added to 1.03MPa, and the temperature was raised to 50°C. After reacting at 50°C at a constant temperature and pressure for 0.5h, the ethylene in the kettle was replaced with nitrogen and the pressure was raised to 2MPa. Then 12g methacrylic acid was added, the temperature was raised to 125°C, and the reaction was continued for 5h before cooling and discharging. The assessment results are shown in Table 2.

[0077] Example 5

[0078] 1. Preparation of catalyst: In a 250mL four-necked flask equipped with a temperature controller, a stirrer, a reflux condenser, and nitrogen-purged and protected, 80mL of tetrahydrofuran (THF), 2.1g of magnesium chloride and 0.5mL of TiCl4 were added successively under stirring, and the temperature was raised to 65°C under stirring, and the reaction was carried out under constant temperature reflux for 4 hours to obtain a mother liquor; then 5.0g of silica gel and 5.0g of benzoyl peroxide were added, and constant temperature reflux stirring was continued at 65°C for 2 hours to completely disperse the silica gel in the mother liquor to obtain a slurry suspension; in a closed-loop circulating airflow spray dryer, nitrogen with an inlet temperature of 140°C was introduced into the spray dryer, and the obtained slurry suspension was added to the circulating dryer, the outlet temperature was 95°C, and the inlet nitrogen flow rate was controlled to be 32.5m 3 / h to obtain a solid catalyst component, some of its physical property parameters are shown in Table 1.

[0079] 2. Ethylene slurry polymerization and grafting reaction: 1L hexane was added to a 2L polymerization kettle that was first purged with nitrogen and then with hydrogen, and 1mL triethylaluminum (1M) and 100mg dry powder catalyst were added at the same time. Hydrogen was added to 0.28MPa. After hydrogenation, ethylene was added to 1.03MPa, and the temperature was raised to 50°C. After reacting at 50°C at a constant temperature and pressure for 0.5h, the ethylene in the kettle was replaced with nitrogen and the pressure was raised to 2MPa. Then 12g methyl methacrylate was added, the temperature was raised to 125°C, and the reaction was continued for 5h before cooling and discharging. The assessment results are shown in Table 2.

[0080] Example 6

[0081] 1. Preparation of catalyst: In a 250mL four-necked flask equipped with a temperature controller, a stirrer, a reflux condenser, and nitrogen-purged and protected, 80mL of tetrahydrofuran (THF), 2.1g of magnesium chloride and 0.5mL of TiCl4 were added successively under stirring, and the temperature was raised to 65°C under stirring, and the reaction was carried out under constant temperature reflux for 4 hours to obtain a mother liquor; then 3.0g of silica gel and 6.0g of benzoyl peroxide were added, and constant temperature reflux stirring was continued at 65°C for 2 hours to completely disperse the silica gel in the mother liquor to obtain a slurry suspension; in a closed-loop circulating airflow spray dryer, nitrogen with an inlet temperature of 140°C was introduced into the spray dryer, and the obtained slurry suspension was added to the circulating dryer, the outlet temperature was 95°C, and the inlet nitrogen flow rate was controlled to 32.5m 3 / h to obtain a solid catalyst component, some of its physical property parameters are shown in Table 1.

[0082] 2. Ethylene slurry polymerization and grafting reaction: 1L hexane was added to a 2L polymerization kettle that was purged with nitrogen first and then hydrogen, and 1mL triethylaluminum (1M) and 100mg dry powder catalyst were added at the same time. Hydrogen was added to 0.28MPa. After hydrogenation, ethylene was added to 1.03MPa, and the temperature was raised to 50°C. After reacting at 50°C at a constant temperature and pressure for 0.5h, the ethylene in the kettle was replaced with nitrogen and the pressure was raised to 2MPa. Then 6g methyl methacrylate was added, the temperature was raised to 125°C, and the reaction was continued for 5h before cooling and discharging. The assessment results are shown in Table 2.

[0083] Example 7

[0084] The catalyst was prepared according to the method of Example 5, except that during spray drying, the inlet nitrogen flow rate was controlled at 20.0 m 3 / h. Some of its physical characteristics are shown in Table 1.

[0085] According to the method of Example 5, ethylene slurry polymerization and grafting reaction were carried out.

[0086] Comparative Example 1

[0087] In a 1L reactor with a stainless steel jacket heating belt stirring, 50g of high-density polyethylene, 4g of methacrylic acid, 4g of benzoyl peroxide and an appropriate amount of interfacial wetting agent were added, the reaction temperature was set to 100°C, and the material was discharged after reacting for 3h. It was then washed with xylene and anhydrous ethanol, filtered and dried to obtain a product sample. Its physical properties are shown in Table 2.

[0088] Comparative Example 2

[0089] In a 1L reactor with a stainless steel jacket heating belt stirring, 50g of high-density polyethylene, 4g of methacrylic acid, 4g of azobisisobutyronitrile and an appropriate amount of interfacial wetting agent were added, the reaction temperature was set to 100°C, and the material was discharged after reacting for 3h, and then washed with xylene and anhydrous ethanol, filtered and dried to obtain a product sample. Its physical properties are shown in Table 2.

[0090] Comparative Example 3

[0091] The catalyst was prepared according to the method of Example 5, except that benzoyl peroxide was not added during the preparation process. Some of its physical property parameters are shown in Table 1.

[0092] Ethylene slurry polymerization and grafting reaction were carried out according to the method of Example 1, except that 5 g of benzoyl peroxide was added at the same time as methyl methacrylate to obtain a product sample. The evaluation results are shown in Table 2.

[0093] Table 1 Some physical parameters of catalyst

[0094]

[0095]

[0096] Table 2. Some physical properties of grafted polyethylene

[0097]

[0098] It can be seen from the data in Table 1 that the metal loading and free radical content of the Ziegler-Natta catalysts for ethylene polymerization and in-situ grafting obtained in Examples 1 to 7 of the present invention can be adjusted according to the formula, and the particle size can be regulated by the slurry formula and process conditions, so that smaller polyethylene particles can be obtained, which is more conducive to improving the grafting reaction rate and has a narrower particle size distribution.

[0099] In Example 7, the catalyst size becomes larger than that in Example 5 by changing the spray drying conditions (Table 1). The polymer particle size obtained by such a catalyst also becomes larger, which also reduces the grafting efficiency, indicating the controllability of the catalyst particle size.

[0100] It can be seen from the data in Table 2 that the initiator content in Examples 1 to 7 is much lower than that in the comparative example, and the gel content of the obtained product is lower; the present invention can directly obtain polar grafted polyethylene with higher grafting rate and lower gel rate by a one-step method under the condition of less initiator and polar monomer dosage; and due to the advantages of the catalyst and the polymer preparation method, the obtained polymer does not need to be dried and separated, the process is short, and the polymer bulk density is higher, achieving unexpected technical effects.

[0101] The other conditions of Comparative Example 3 are consistent with those of Example 5, but the initiator is not in the catalyst but added during the grafting reaction. Thus, the initiator cannot be uniformly introduced into the polymer during the first polymerization reaction, resulting in low grafting efficiency (Table 2), indicating that adding the initiator to the catalyst and uniformly dispersing it in the polymer through the polymerization reaction achieves an unexpected technical effect.

[0102] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

[0103] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definition in this specification shall prevail.

[0104] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.

[0105] The endpoints and any values ​​of the scope disclosed in the present application document are not limited to the precise scope or value, and these scopes or values ​​should be understood to include values ​​close to these scopes or values. For numerical ranges, between the endpoint values ​​of each scope, between the endpoint values ​​of each scope and a separate point value, and between separate point values, one or more new numerical ranges can be combined with each other, and these numerical ranges should be considered as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be considered as specifically disclosed in this article.

[0106] In the context of the present specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.

[0107] Moreover, any embodiment described in this document may be freely combined with one or more other embodiments described in this document, and the technical solutions or technical ideas formed thereby are deemed to be part of the original disclosure or original record of the present invention, and should not be regarded as new content that has not been disclosed or anticipated in this document, unless a person skilled in the art considers that the combination is obviously unreasonable.

Claims

1. A Ziegler-Natta catalyst comprising a blended component and / or a reaction product of the following raw materials: A carrier, a titanium source, a magnesium source, an electron donor and a free radical initiator.

2. The Ziegler-Natta catalyst according to claim 1, characterized in that The carrier is selected from inorganic oxide carriers, preferably selected from silicon oxide and / or aluminum oxide, preferably silicon dioxide; and / or, The particle size of the carrier is 0.01 to 5 μm, preferably 0.01 to 2 μm; and / or, The free radical initiator is selected from at least one of azo and peroxide initiators, preferably selected from at least one of benzoyl peroxide, diisopropylbenzene peroxide, di-tert-butyl peroxide, tert-butyl hydroperoxide, tert-butyl perbenzoate, diisobutyl peroxydicarbonate, azobisisobutyronitrile and azobisisoheptylonitrile.

3. The Ziegler-Natta catalyst according to claim 1, characterized in that The titanium source is a titanium-containing compound; preferably, the titanium-containing compound is at least one selected from titanium halide, a product of aluminum reduction of titanium halide, and a product of magnesium reduction of titanium halide; and / or, The magnesium source is a magnesium halide; preferably, the magnesium halide is selected from at least one of magnesium fluoride, magnesium chloride, magnesium bromide and magnesium iodide; and / or, The electron donor is selected from at least one of C1-C4 saturated fatty carboxylic acid alkyl esters, C7-C8 aromatic carboxylic acid alkyl esters, C2-C6 fatty ethers, C3-C4 cyclic ethers and C3-C6 saturated fatty ketones.

4. The Ziegler-Natta catalyst according to any one of claims 1 to 3, characterized in that Based on the total weight of the Ziegler-Natta catalyst being 100wt%, the Ziegler-Natta catalyst comprises: titanium element: 0.5-4wt%; magnesium element: 2-8wt%; electron donor: 10-35wt%; free radical initiator: 10-60wt%; carrier: 10-60wt%; and / or, The average particle size of the Ziegler-Natta catalyst is 7 to 100 μm, preferably 8 to 50 μm; and / or, The particle size distribution of the Ziegler-Natta catalyst is less than 2, preferably less than 1.

5.

5. A method for preparing the Ziegler-Natta catalyst according to any one of claims 1 to 4, comprising the following steps: (1) mixing raw materials including a titanium source, a magnesium source, an electron donor, a free radical initiator, a carrier and an optional organic solvent to obtain a slurry suspension; (2) spray drying the slurry suspension obtained in step (1) to obtain the Ziegler-Natta catalyst.

6. The preparation method according to claim 5, characterized in that: The preparation of the slurry suspension in step (1) comprises: firstly mixing a titanium source, a magnesium source and an electron donor, treating at 20-85° C. for 0.5-3 hours to obtain a mother liquor; adding a carrier and a free radical initiator during or after the preparation of the mother liquor, and mixing for 2-12 hours; and / or, The spray drying conditions in step (2) are: inlet temperature 50-200°C, outlet temperature 30-150°C; and / or, The air flow rate of the spray drying nozzle in step (2) is 10-50m 3 / h.

7. The preparation method according to claim 5 or 6, characterized in that: In step (1), the amount of the electron donor is 5 to 100 mL, preferably 10 to 50 mL, relative to 1 g of the carrier; and / or the mass ratio of the carrier to the free radical initiator is (0.1 to 50):1, preferably (0.3 to 10):1; and / or the molar ratio of the titanium element in the titanium source to the magnesium element in the magnesium source is (0.1 to 0.5):1; and / or the mass ratio of the carrier to the magnesium source is (0.5 to 6):

1.

8. A catalyst for olefin polymerization, comprising: (A) the Ziegler-Natta catalyst according to any one of claims 1 to 4 or the Ziegler-Natta catalyst obtained by the preparation method according to any one of claims 5 to 7; (B) The general formula is A1R b X' 3b An organoaluminum compound, wherein R is hydrogen or a hydrocarbon group having 120 carbon atoms; X' is a halogen; and 0<b≤3.

9. The catalyst according to claim 8, characterized in that The organoaluminum compound is at least one selected from triethylaluminum, triisobutylaluminum, tri-n-hexylaluminum, tri-n-octylaluminum and diethylaluminum monochloride; and / or, The molar ratio of the organic aluminum compound to the titanium element in the Ziegler-Natta catalyst is (5-1000):

1.

10. Use of the Ziegler-Natta catalyst according to any one of claims 1 to 4, or the Ziegler-Natta catalyst prepared by the preparation method according to any one of claims 5 to 7, or the catalyst according to claim 8 or 9 in olefin polymerization.

11. The use according to claim 10, characterized in that: The application of the Zigler-Natta catalyst in olefin polymerization includes: 1) Ethylene is reacted with a Ziegler-Natta catalyst and a general formula of A1R b X' 3b contacting an organic aluminum compound, and / or contacting ethylene with the catalyst according to claim 8 or 9 to carry out ethylene polymerization to obtain a polyethylene powder containing a free radical initiator; 2) contacting the polar monomer with the polyethylene powder containing the free radical initiator obtained in 1) so that the free radical initiator initiates in-situ grafting of the polar monomer on the polyethylene; preferably, The polar monomer is a compound containing a double bond and a polar group, and more preferably at least one of acrylic acid and its derivatives or esters, maleic anhydride or esters, maleate, alkenyl bisphenol A ether, acrylonitrile, styrene and its homologues, and glycidyl methacrylate.

Citation Information

Patent Citations

  • Solid catalyst component used for olefin polymerization, preparation method of solid catalyst component, catalyst and application of catalyst

    CN110016095A

  • Catalyst component for olefin polymerization or copolymerization as well as preparation method and application of catalyst component

    CN113563496A

  • Polymerizing monomer in presence of polymer containing electrophilic moiety using Ziegler-Natta catalyst

    US4525538A